2017
DOI: 10.1038/s41598-017-03176-z
|View full text |Cite
|
Sign up to set email alerts
|

The Connection of the Genetic, Cultural and Geographic Landscapes of Transoxiana

Abstract: We have analyzed Y-chromosomal variation in populations from Transoxiana, a historical region covering the southwestern part of Central Asia. We studied 780 samples from 10 regional populations of Kazakhs, Uzbeks, Turkmens, Dungans, and Karakalpaks using 35 SNP and 17 STR markers. Analysis of haplogroup frequencies using multidimensional scaling and principal component plots, supported by an analysis of molecular variance, showed that the geographic landscape of Transoxiana, despite its distinctiveness and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
1
23
1
Order By: Relevance
“…Considering that J1 is thought to originate from a geographical zone that includes northeastern Syria, northern Iraq and eastern Turkey, from where it expanded to the rest of the Near East and North Africa, such high prevalence of J1 among Iraqi Arabs is indicative of their indigenous nature [ 45 ]. There are also a number of earlier investigations on the paternal lineages of various Turkmen populations [ 25 , 26 , 39 , 46 ]. However, a distinction should perhaps be made between the Turkic populations from Turkmenistan in Central Asia and elsewhere, such as in Northern Iraq and Northern Syria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that J1 is thought to originate from a geographical zone that includes northeastern Syria, northern Iraq and eastern Turkey, from where it expanded to the rest of the Near East and North Africa, such high prevalence of J1 among Iraqi Arabs is indicative of their indigenous nature [ 45 ]. There are also a number of earlier investigations on the paternal lineages of various Turkmen populations [ 25 , 26 , 39 , 46 ]. However, a distinction should perhaps be made between the Turkic populations from Turkmenistan in Central Asia and elsewhere, such as in Northern Iraq and Northern Syria.…”
Section: Discussionmentioning
confidence: 99%
“…At least the Northern Iraqi Turkmen, although still Turkic and thus with historical links with Central Asia, have even closer links with the Turkic populations from Anatolia and/or Azerbaijan/Northwestern Iran. Earlier investigations on the Turkmen population in Afghanistan, Uzbekistan and Iran, suggested that haplogroup Q was the most prevalent accounting for 34%, 73% and 43%, in that order [ 25 , 26 , 39 ]. An earlier study from the Turkmenistan population per se also exists, albeit of relatively poor Y-SNP typing resolution, whereby the most prevalent haplogroups observed were P(xR1a), J and N(x3) with the frequencies of 52%, 24% and 10%, in that order [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three main directions of population genetic studies, including the study of autosomal markers, the study of mitochondrial DNA (mtDNA), and the study of Y chromosome polymorphism. The profiles of mtDNA and Y chromosome polymorphism in the Kazakh population are well characterized, 19 , 20 whereas data on autosomal markers are lacking. As a result, allele distribution is well studied in Caucasian populations but poorly understood in Central Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in one of Buryat clans, namely Ekhirids, hg C2 frequency is 88 % (Y-base); in Kazakhs from different regions of Kazakhstan, total occurrence of hg C2 variants averages between 17 and 81 % (Abilev et al, 2012;Zhabagin et al, 2013Zhabagin et al, , 2014Zhabagin et al, , 2017 …”
Section: "Genetic Portrays" Of Mongush and Oorzhak Clansmentioning
confidence: 99%